Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1155/2018/8414605
|View full text |Cite
|
Sign up to set email alerts
|

Model Analysis of Digital Models in Moderate to Severe Crowding: In Vivo Validation and Clinical Application

Abstract: Objective We investigated the suitability of intraoral-scan models for measuring tooth dimensions and the amount of crowding in patients with severe tooth crowding. Materials and Methods Fifty-eight patients who had undergone intraoral scans for diagnosis were included. Cast models were divided into two groups depending on the amount of crowding, as determined by initial caliper-based measurements (mild crowding [MC] group: <3.0 mm; severe crowding [SC] group: >4.5 mm). Twenty maxillary models and 20 mandibula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
2
16
0
1
Order By: Relevance
“…Differences between plaster and intraorally scanned models were up to 0.86 mm for maxilla and 0.55 mm for mandible with statistically significant differences. Authors concluded that recorded differences are not clinically significant and that all three methods can be used in practice, regardless of the severity of crowding [26]. Comparison of these results and results presented in our paper indicates that recorded discrepancies between methods are comparable, with the note of no statistically significant difference being present in our results for complete arches.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Differences between plaster and intraorally scanned models were up to 0.86 mm for maxilla and 0.55 mm for mandible with statistically significant differences. Authors concluded that recorded differences are not clinically significant and that all three methods can be used in practice, regardless of the severity of crowding [26]. Comparison of these results and results presented in our paper indicates that recorded discrepancies between methods are comparable, with the note of no statistically significant difference being present in our results for complete arches.…”
Section: Discussionsupporting
confidence: 71%
“…Pri poređenju merenja na gipsanom modelu i intraoralno skeniranom modelu dobijena prosečna odstupanja su iznosila do 0,86 mm za mak-silu i 0,55 mm za mandibulu, uz pronađene statistički značajne razlike. Autori zaključuju da razlike u merenjima nisu klinički značajne i da je moguća upotreba sva tri metoda u kliničkoj praksi bez obzira na stepen teskobe [26]. Poredeći navedene rezultate sa rezultatima prezentovanim u ovom radu, vidljivo je da su odstupanja približno istih vrednosti, uz razliku da u našem slučaju nije pronađena statistički značajna razlika za cele vilice.…”
Section: Diskusijaunclassified
“…Also the malocclusion has an effect on digital orthodontic models measurements. Significant differences in the amount of crowding due to the accumulation of errors were reported [20]. According to Bocklet et.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoral scanners (IOS) are used in dentistry as a convenient method of taking impressions [1][2][3][4][5][6]. Orthodontic tooth movement can also be easily evaluated using IOS [7][8]. Through the dental model acquired at the time of re-diagnosis of patients undergoing orthodontic treatment, not only the relationship between the entire dentition and the arch, but also the position of the bracket is reevaluated.…”
Section: Introductionmentioning
confidence: 99%